2021
DOI: 10.1021/acsomega.1c00824
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation for Monitoring the Time-Variant Mechanical Strength of Drug-Loaded Collagen Hydrogel Regulated by Hydroxyapatite Nanoparticles

Abstract: Hydroxyapatite nanoparticle-complexed collagen (HAP/Col) hydrogels have been widely used in biomedical applications as a scaffold for controlled drug release (DR). The time-variant mechanical properties (Young’s modulus, E ) of HAP/Col hydrogels are highly relevant to the precise and efficient control of DR. However, the correlation between the DR and the E of hydrogels remains unclear because of the lack of a nondestructive and continuous measuring system. To reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, both XRD and FTIR spectroscopy analyses indicated a phase transition from HAP to tricalcium phosphate (TCP) beyond the sintering temperature of 500 °C; a new peak appeared at 31.1° in the diffraction pattern and 1120 cm − 1 in the IR transmission spectrum (Fig. 3 c and d) [ 67 69 , 71 ]. As our study focused on the investigation of the effect of natural bone-mimicking nanopores in the HAP scaffold rather than the influence of the phase transition from HAP to TCP, SNPs sintered above 500 °C were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…However, both XRD and FTIR spectroscopy analyses indicated a phase transition from HAP to tricalcium phosphate (TCP) beyond the sintering temperature of 500 °C; a new peak appeared at 31.1° in the diffraction pattern and 1120 cm − 1 in the IR transmission spectrum (Fig. 3 c and d) [ 67 69 , 71 ]. As our study focused on the investigation of the effect of natural bone-mimicking nanopores in the HAP scaffold rather than the influence of the phase transition from HAP to TCP, SNPs sintered above 500 °C were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, NP-embedded hydrogel complexes have attracted considerable attention because of the advantages of hydrogels, such as biodegradability, biocompatibility and non-toxicity, which can be combined with the unique properties of NPs [ 12 , 13 , 14 , 15 , 16 ]. For example, Jung et al demonstrated that the mechanical properties of a collagen hydrogel could be modulated by adding hydroxyapatite NPs [ 17 ]. Arno et al demonstrated improved adhesion and resistance to breakage in calcium alginate hydrogels using poly( L -lactide)-based NPs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is a multi-functional device that can analyze a sample’s morphology, mechanical strength, and surface charge by its nano-scale cantilever [ 36 , 37 , 38 , 39 ]. In this report, we demonstrate a robust mechanical characterization of histological specimens using atomic force microscopy (AFM) indentation for discrimination among normal, benign nevus, and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…As such, our goals were to verify (i) whether the mechanical characterization of the histological specimen would be consistent with the results from conventional histopathological analysis and (ii) whether it could provide abundant information about benign versus malignant epidermal tissues, complementing the traditional histopathological examinations. Atomic force microscopy (AFM) is a multi-functional device that can analyze a sample's morphology, mechanical strength, and surface charge by its nano-scale cantilever [36][37][38][39]. In this report, we demonstrate a robust mechanical characterization of histological specimens using atomic force microscopy (AFM) indentation for discrimination among normal, benign nevus, and melanoma.…”
Section: Introductionmentioning
confidence: 99%